Adaptive leadership behaviors and their impact on building strategic differentiation for tourism services: an analytical exploratory study of travel and tourism companies in the governorates of the Middle Euphrates. - البغدادي, عادل هادي حسين; الخزعلي, معتز حميد رحيم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Purpose: The current research aims to test the effect of adaptive leadership behaviors in building strategic differentiation of tourism service through a sample of employees in travel and tourism companies in the Middle Euphrates region. Methodology/Design: The problem of the study was embodied in a number of questions, the most important of which is whether there is an effect of adaptive leadership behaviors in building the strategic differentiation of tourism service. The study relied on the descriptive approach because of its advantages, as it allows for an accurate and comprehensive description of the phenomenon, and a variety of tools can also be used (interviews, questionnaires). ). The study used questionnaires as a tool for collecting data. (170) questionnaires were distributed to employees in the surveyed companies. The retrieved questionnaires (160) and the excluded ones (6), which were subjected to statistical analysis (154), were questionnaires. The study relied on statistical programs (SPSS v.24) and (SMART PLS v.4) Cognitive conclusions and results: Adaptive leadership behaviors are practices that enable organizations to develop their ability to adapt to a complex environment by mobilizing human resources and directing them to achieve the organization's desired goals. The results showed a significant effect of the independent variable (adaptive leadership behaviors) on the dependent variable (strategic service differentiation). This indicates that adaptive leadership behaviors contribute to building strategic differentiation by creating appropriate conditions for human resources to work within an effective organizational environment.